Determinan Pernikahan Dini pada Remaja Putri - Amu, Melisawati (Politeknik Kesehatan Kementrian Kesehatan Gorontalo, 2020)
Early marriage still occurs due to various factors. This study aims to analyze and identify the factors that influence marriage in young women. This research method uses an analytical survey with a casecontrol design. The population in this study was 169 young women. The sample in this study was 64 young women according to the inclusion criteria. Data analysis in this study used the Chi-Square statistical test. The results of the study using Chi-Square showed that education (0.001) < (0.05), parental income (0.008) < (0.05), pregnancy out of wedlock (0.000) < (0.05). The conclusion is that there is a significant effect of education level, parental income, and pregnancy outside of marriage on early marriage in adolescent girls.